Efficiency of application of antioxidants from group sterically hindered phenols by retina photodegradation - A. A. Zhdankina; M. B. Plotnikov; G. A. Kon; I. S. Ivanov; Ye. Yu. Varakuta; A. V. Kuchin; I. V. Chukicheva; S. V. Logvinov (Бюллетень сибирской медицины, 2010)
Renoprotective effect of antioxidants from group sterically hindered phenols (thiophane, dibornol) in white nondescript male rats (n = 55) subjected to influence of light intensity level 6 000 lx during 6 h was demonstrated. Course intragastric administration of thiophane limited of destructive changes in the retina, but didn’t bring to disappearance of lesion focuses. Dibornol prevented progression of local changes in the retina, contributed to decrease destruction of neurosensory cells, pigment epithelium and neurons of internal layer.